The sacred bridge - Hillerman, Anne, 1949- (Hillerman, Tony. Leaphorn and Chee novel, 2022)
Sergeant Jim Chee's vacation to beautiful Antelope Canyon and Lake Powell has a deeper purpose. He's on a quest to unravel a sacred mystery his mentor, the Legendary Lieutenant Joe Leaphorn, stumbled across decades earlier. Chee's journey takes a deadly turn when, after a prayerful visit to the sacred Rainbow Bridge, he spots a body floating in the lake. The dead man, a Navajo with a passion for the canyon's ancient rock art, lived a life filled with many secrets. Discovering why he died and who was responsible involves Chee in an investigation that puts his own life at risk. Back in Shiprock, Officer Bernadette Manuelito is driving home when she witnesses an expensive sedan purposely kill a hitchhiker. The search to find the killer leads her to uncover a dangerous chain of interconnected revelations involving a Navajo Nation cannabis enterprise. But the evil that is unleashed jeopardizes her mother and sister Darleen, and puts Bernie in the deadliest situation of her law enforcement career.